Analysis of Anxiety and Depression Status in Patients Undergoing Radiotherapy During the COVID-19 Epidemic - Yang, Liping; Yang, Jing; He, Jian; Zhou, Yan; Zhang, Yangyang; Sun, Bin; Gao, Jing; Qian, Liting (Frontiers in Psychiatry, 2021)
Background: The 2019 coronavirus (COVID-19) has caused a global pandemic and disrupted millions of lives. Cancer patients are a special group at greater risk of contracting viruses. This study aimed to evaluate the anxiety and depression status of cancer patients undergoing radiotherapy during the COVID-19 epidemic. Methods: 396 cancer patients who underwent radiotherapy were enrolled in this study. The self-rating anxiety scale (SAS) and self-rating depression scale (SDS) were used to evaluate patient anxiety and depression, respectively. 373 cancer patients completed the questionnaires. Results: During the COVID-19 outbreak, the incidence of anxiety and depression in cancer patients was 34.9% and 33.8%, respectively. Approximately 31.4% of tumor radiotherapy patients had anxiety and depression. Based on univariate analysis, age, work status, education level, and clinical stage were related to anxiety and depression in cancer patients. Based on multiple regression analysis, age and clinical stage were related to anxiety, but only age was related to depression. Conclusions: Due to the COVID-19 pandemic, cancer patients experienced increased psychological problems. Our results have contributed to a better understanding of these psychological problems in cancer patients and provide a basis for psychological counseling and intervention.